It chooses you - July, Miranda 1974- (McSweeneys Books, 2011)
L.A. screenwriter, performance artist, and author, takes to the streets to meet the folks advertising their cheap wares in the local "PennySaver" classifieds shopper. Their stories are humorous, intriguing, and sometimes moving, and ultimately, surprisingly helpful in shaping the film she is trying to complete